THE IMPORTANCE OF STATISTICAL METHODS IN ANALYZING RESEARCH FINDINGS. (Journal of Universal Science Research, 2025)
This article examines the essential role of statistical methods in analyzing research findings across various scientific disciplines. It highlights how statistical techniques enable researchers to organize data, identify meaningful patterns, ensure the reliability and validity of results, and draw evidence-based conclusions. The paper also discusses the contribution of descriptive and inferential statistics to the interpretation of complex datasets, emphasizing their importance in enhancing the accuracy, transparency, and scientific value of research outcomes. Furthermore, the study outlines common challenges researchers face when selecting and applying statistical methods, offering practical considerations for improving data analysis practices.